Implementasi Metode Lalaran untuk Meningkatkan Kemampuan Menghafal Kitab Al- Imrithi Santri di Pondok Pesantren An- Nawawi 03 Kebumen - Siti Ulfah Afndoliyah; Faisal Faisal (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to thoroughly analyze (1) the implementation process of the Lalaran method in the context of memorizing nazham Al-Imrithi, and (2) the level of improvement in students’ memorization skills after applying the Lalaran method at An-Nawawi 03 Islamic Boarding School (PP) Kebumen. The research employed a descriptive qualitative approach, seeking to holistically portray the realities in the field. Research subjects included the Head of the Boarding School, the Al-Imrithi Kitab Instructor, and active female students (santriwati). Data were collected through participatory observation, in-depth interviews, and documentation study. The results indicate that the implementation of the Lalaran method at PP An- Nawawi proceeds through three critical phases: preparation, involving the determination of rhythm (irama); execution, divided into main and flexible times; and evaluation, consisting of weekly recitations and final examinations. The method proves effective not only in increasing the quantity of memorization but also the quality of memory retention, fostering collective discipline, and overcoming the challenge faced by students who previously struggled to meet their memorization targets. Lalaran effectively serves as a contextual and pesantren tradition-based learning solution.